Examination of Correlation between Histidine and Cadmium Absorption by Eleagnus angustifolia L., Vitisvinifera L. and Nerium oleander L. Using HPLC-MS and ICP-MS - Ozen, Sukran Akkus; Yaman, Mehmet (Office Spectroscopy & Spectral Analysis, 2016)
In this study, HPLC-MS and ICP-MS methods were used for the determination of histidine and cadmiumin Eleagnusangusti folic L., Vitisvinifera L. and Nerium oleander L. leaves taken from industrial area including Gaziantep and Bursa cities. To histidine determination by HPLC-MS, flow rate of mobile phase, fragmentor potential, injection volume and column temperature were optimized as 0. 2 mL . min(-1), 70 V, 15 mu L and 20 degrees C, respectively. For extraction of histidine from plants, distilled water was used by applying on 90 degrees C and 30 min. The concentrations (as mg . kg(-1)) of histidine were found to be in range of 8 similar to 22 for Elea gnusangusti folia L., 10 similar to 33 for Vitisvini f era L. and 6 similar to 11 for Nerium oleander L. The concentrations of cadmium were found to be in ranges of 6 similar to 21 mu g . kg(-1) for Vitisvini f era L. 15 similar to 110 mu g . kg(-1) for Elea gnusangusti folia L. and 63 similar to 218 mu g . kg(-1) for Nerium oleander L.
Keywords: Histidine; Cadmium; Hyperaccumulator plants; ICP-MS; HPLC-MS